Severe thrombocytopenia induced by a occlude for PDA: A medical device surveillance case report - Lechuga-Noa, Víctor E. (2023)
Introduction: Patent ductus arteriosus (PDA) is a congenital heart condition of special interest. Interventional occlusion is the treatment of choice; however, a PDA occlude, used in this procedure, is a medical device that rarely could lead to adverse events such as hemorrhage, thrombocytopenia, etc. Case report: We present a case of a pediatric patient with severe thrombocytopenia after surgery. During her hospitalization, platelet levels remained lower and, finally, she was fully recovered without any hematological manifestation. The case was reported as a suspected adverse incident related to PDA occlude. Conclusion: After performing a cause-root analysis, we concluded that the size of the PDA occlude may be the main cause of thrombocytopenia.  This case demonstrates that medical devices could lead to adverse events. Thus, it is important for clinicians to implement medical device surveillance, mainly for high-risk medical devices.